Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1128/aac.01664-08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low-Level Resistance to Fluoroquinolones Due to qnrA1 and qnrS1 Genes or a gyrA Mutation on Ciprofloxacin Bactericidal Activity in a Murine Model of Escherichia coli Urinary Tract Infection

Abstract: We investigated the impact of low-level resistance to fluoroquinolones on the bactericidal activity of ciprofloxacin in a murine model of urinary tract infection. The susceptible Escherichia coli strain CFT073 (ciprofloxacin MIC [CIP MIC] of 0.008 g/ml) was compared to its transconjugants harboring qnrA1 or qnrS1 and to an S83L gyrA mutant. The three derivatives showed similar low-level resistance to fluoroquinolones (CIP MICs, 0.25 to 0.5 g/ml). Bactericidal activity measured in vitro after 1, 3, and 6 h of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 39 publications
4
50
1
5
Order By: Relevance
“…These results suggested that the contribution of qnrA to bacterial survival is not equivalent in all serotypes of E. coli strains. To date, some investigators have reported that in the present of CIP, E. coli isolates with qnr could survive longer than those without qnr (13,21). In the present study, we also confirmed that the acquisition of qnrA contributed to increased bacterial survival under exposure to lethal CIP concentrations in E. coli strains displaying certain O-serotypes (O1, O6, and O25b).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…These results suggested that the contribution of qnrA to bacterial survival is not equivalent in all serotypes of E. coli strains. To date, some investigators have reported that in the present of CIP, E. coli isolates with qnr could survive longer than those without qnr (13,21). In the present study, we also confirmed that the acquisition of qnrA contributed to increased bacterial survival under exposure to lethal CIP concentrations in E. coli strains displaying certain O-serotypes (O1, O6, and O25b).…”
Section: Resultssupporting
confidence: 79%
“…To date, 6 groups of Qnr proteins have been identified (QnrA, QnrB, QnrC, QnrD, QnrS, and QnrVC) (11,12). Allou et al evaluated the impact of the acquisition of genes encoding Qnrs, and found that the low-level resistance to FQs conferred by these genes was associated with decreased bactericidal activity of CIP (13). In a preliminary study, we also found that qnrA contributed to improved bacterial survival at lethal CIP concentrations.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Six variants have been identified (qnrA1 to qnrA6). These genes can increase the MIC of fluoroquinolones up to 32-fold in E. coli isolates (Poirel et al, 2006;Allou et al, 2009). In addition, qnrA gene enhances the selection of chromosomal encoded quinolone resistance determinants which confer additional resistance to fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Fluroquinolones act by increasing levels of enzyme-mediated DNA cleavage affecting DNA gyrase enzyme which catalyzes the negative supercoiling of DNA and topoisomerase IV enzyme which decatenates or removes the interlinking of daughter chromosomes at the completion of a round of DNA replication allowing their segregation into daughter cell (Ambrozic et al, 2007;Wang et al, 2009). Quinolone resistance has traditionally been attributed mainly to chromosomal mutations in the gyrA and gyrB genes of DNA gyrase and in parC and parE genes of topoisomerase IV or due to decreased intracellular concentration as a result of decreased permea-bility of the membrane or over expression of efflux pump systems (Poirel et al, 2006;Oktem et al, 2008;Allou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%